Nanocontainers Against Biofouling and Corrosion Degradation of Materials: A Short Review With Prospects - Kordas, George (Frontiers in Nanotechnology, 2022)
The current state of the art in active corrosion prevention is based on the use of macromolecular containers that can store and release corrosion inhibitors particularly to the surface when corrosion develops. These corrosion inhibitor-containing nano- or microcontainers are subsequently infused into coatings, allowing them to self-heal. Especially, nanocontainers for self-healing coatings with controlled corrosion inhibitors, energy storage, cement fracture repair, and antifouling metal protection have recently been developed. Incorporating these nanocontainers into materials in small amounts (e.g., 5–10 wt% in paints) provided anticorrosion protection that was incomparably better than the current approaches. Furthermore, the materials developed had multifunctional properties, including self-healing, antibacterial, and antimicrobial properties. The primary goal of this review was to compile the different research studies that have been published in a variety of publications so that the reader may better understand the potential of these new types of nanotechnology and the prospects for nanocontainers.